Which is better at detecting financial statement fraud: Beneish M-Score or OMI model - Ayati, Eneng Ela Tri; Mulya, Ali Sandy (Proceeding International Conference on Accounting and Finance, 2024)
According to the Association of Certified Fraud Examiners (ACFE), financial statement fraud has the most significant impact in Indonesia. Therefore, the need for the best model in detecting financial statement fraud is crucial. This research examines the influence of the fraud hexagon on the Beneish M-Score model and the Overall Manipulation Indexs (OMI) model in detecting financial statement fraud, as well as comparing which model is the most effective in detecting financial statement fraud. The analytical technique employed in this study involves panel data regression using the Fixed Effect Model and Common Effect Model approaches, utilizing STATA17 software. The population under investigation comprises state-owned enterprises for the period 2017-2021. Sample selection was carried out using the purposive sampling method, resulting in a sample size of 24 companies. The findings indicate that the Beneish M-Score model does not exhibit an influence on the fraud hexagon in detecting financial statement fraud. Conversely, the testing conducted using the OMI method, focusing on elements within the fraud hexagon such as capability, stimulus, and rationalization, shows an influence on financial statement fraud. As a result, the model that holds the most impact in detecting financial statement fraud is the OMI model, due to its greater influence compared to the Beneish M-Score model.